A avaliação da reflexidade/impulsividade em crianças de idade pré-escolar - Maria Cruz, Orlanda (1989)
Reflection-impulsivity is a cognitive style construct which refers to the extent to which a child delays a response when he/she is faced with a problem solving situation whose main feature is a response uncertainty. This study is intended to be a contribution to the assessment of reflection-impulsivity in preschoolers. In this sense the Kansas Reflection-Impulsivity Scale for Preschoolers (KRISP) was applied on a sample of 190 children ranging from three to five years of age. The ten items of the instrument were analysed (hierarchy and homogeneity of the items)as well as the reliability of the two possible scores: latency and errors. Test-retest and internal consistency procedures were used. The results were analysed taking in account the three age groups (three, four and five years old).